ECO-FRIENDLY MANAGEMENT OF POSTHARVEST DISEASES OF APPLE FRUITS: AN OVERVIEW - Lenuța CHIRA; Elena DELIAN; Liliana BĂDULESCU; Adrian CHIRA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Apples (Malus × domestica Borkh.) are the most economically important fruits over the world due to their nutritional and bioactive constituents, with significant value for human healthy. Maintaining these attributes during the post-harvest period is a major concern of all those involved in the field, including researchers. In the present synthesis, the results obtained in the last period of time are reviewed, regarding the sustainable management of post-harvest apples diseases, considering the eco-friendly approaches applied both in the pre harvest period and after the fruit harvest. Promising results were obtained regarding: (i) improving plants growing environmental conditions and pre harvest practices using fungicides and the application of complementary, environmentally friendly measures; (ii) exploring the epiphytic and endophytic flora with a view to some microorganisms exploitation as biological control agents; (iii) nanomaterials using and of plant extracts, as well as of some resistance chemical inducers; (iv) genetic engineering, omics-based approaches and machine learning algorithms. With a view to the successful implementation of the most appropriate innovative strategies for apples fruits diseases post-harvest management it is necessary to continue such studies through a close collaboration between researchers and practitioners.